PENERAPAN MODEL PEMBELAJARAN MAKE A MATCH DALAM MENINGKATKAN KETERAMPILAN MENULIS TEKS PROSEDUR PESERTA DIDIK KELAS XI SMA NEGERI 16 BULUKUMBA - Sasmi Utami; Yuni Yuliani; Riswandi R (Jurnal Pendidikan Sang Surya, 2021)
This study aims to determine the improvement of writing procedural text skills in participants through the application of the Make a Match learning model to Class XI students of SMA Negeri 16 Bulukumba. This research is a classroom action research that was carried out for two cycles, each cycle consisting of four stages, namely: planning, implementation, observation or evaluation, and reflection. Data collection techniques used in the form of tests and non-tests. The test technique is in the form of a procedure text writing test which is carried out at the end of each cycle. While the non-test technique is in the form of observing student activities in each meeting, observing attitudes in each cycle, and documentation. The results showed that there was an increase in the procedural text writing skills of Class XI students of SMA Negeri 16 Bulukumba by applying the Make a match learning model, this was seen in the students' learning mastery which increased significantly in the second cycle compared to the first cycle. The test results in the first cycle were obtained. The results were 10 students (31.2 percent) who scored in the complete category and 22 students (68.8 percent) who scored in the incomplete category. While in the second cycle, 26 students (81.3 percent) completed and 6 students (18.7 percent) did not complete. classical completeness of Indonesian learning outcomes is 81.3 percent. Based on the results of this study, it can be concluded that the Make a match learning model is proven to be able to improve procedural text writing skills.